2019
DOI: 10.1159/000500090
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the <b><i>Listeria monocytogenes</i></b> Cellobiose Transport Components and Their Impact on Virulence Gene Repression

Abstract: Background: Many bacteria transport cellobiose via a phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS). In Listeria monocytogenes, two pairs of soluble PTS components (EIIA Cel1 /EIIB Cel1 and EIIA Cel2 /EIIB Cel2) and the permease EIIC Cel1 were suggested to contribute to cellobiose uptake. Interestingly, utilization of several carbohydrates, including cellobiose, strongly represses virulence gene expression by inhibiting PrfA, the virulence gene activator. Results: The LevR-like transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
1
13
1
Order By: Relevance
“…After ilo knockout, the expression levels of most of the virulence genes were up-regulated but were still higher than those of LI. Our results were not completely consistent with the experimental results of Cao et al [ 36 ]. We observed that the downregulation of CelA and CelB after ilo knockout not only down-regulated the cellobiose-induced repression of virulence genes but also down-regulated glucose-induced repression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…After ilo knockout, the expression levels of most of the virulence genes were up-regulated but were still higher than those of LI. Our results were not completely consistent with the experimental results of Cao et al [ 36 ]. We observed that the downregulation of CelA and CelB after ilo knockout not only down-regulated the cellobiose-induced repression of virulence genes but also down-regulated glucose-induced repression.…”
Section: Discussioncontrasting
confidence: 99%
“…The two-component system response regulator VirR is the second most important virulence regulator after PrfA [ 35 ]. A study [ 36 ] found that LM mutants lacking CelC1 and CelR , genes related to disaccharide metabolism in the PTS pathway, or lack of CelA genes, exhibited low cellulosic sugar consumption. Deletion of CelC1 or CelR prevented the repression of virulence genes caused by disaccharides, but this was not applicable to glucose and fructose.…”
Section: Discussionmentioning
confidence: 99%
“…In L. monocytogenes , cellobiose strongly represses virulence gene expression by inhibiting PrfA, the virulence gene activator [14]. Interestingly another study demonstrated the presence of cellobiose PTS operon to be responsible for increased neuro-invasiveness in hypervirulent L.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar Phosphotransferase System (PTS) mediates the uptake and phosphorylation of carbohydrates and controls the carbon and nitrogen metabolism in response to the availability of sugars [53]. In Listeria monocytogenes, two pairs of soluble PTS components (EIIACel1/ EIIBCel1 and EIIACel2/EIIBCel2) and the permease EIICCel1 were responsible for cellobiose uptake and repression of PrfA, which is a virulence gene activator [54]. As a virulence gene, the ptsP mutant caused a decrease in the colonization ability and pathogenicity of Legionella pneumophila [55].…”
Section: The Downregulated Expression Of Virulencerelated Factors Maymentioning
confidence: 99%